Will the Digital Revolution Help or Hurt Employment? : Adaptation a Key to Realizing Job Gains - Raja, Siddhartha; Ampah, Mavis (World Bank, Washington, DC, 2016)
What will technological change deliver in the coming decades? And what can we do to determine the outcome? Technological change in any given society is never smooth and always negotiated. Although both perils and opportunities await, the ultimate result depends on our choices today. Governments, businesses, and individuals have shown that adapting to changing circumstances can alter the consequences of apparently ‘inevitable’ changes. And developing countries can be profoundly affected by changes seemingly limited to the advanced economies; they must adapt to what is actually a global technological playing field. The World Bank’s recently issued World Development Report 2016: digital dividends focuses on strengthening the ‘analog complements’ of the digital economy, including adapting skills to get the most out of the digital revolution. Countries whose governments can facilitate innovation, strengthen education and skill building, and build up the social safety net may be the most likely to benefit from the coming changes.